Exact solutions for a nonstandard viscous Cahn—Hilliard system - Mchedlov-Petrosyan, P.O.; Davydov, L.N. (Reports of the National Academy of Sciences of Ukraine, 2017)
The one-dimensional version of a nonstandard viscous Cahn–Hilliard system (proposed by Colli et al.) for the order parameter and chemical potential with a generally asymmetric polynomial double-well potential is considered. For this system, an exact travelling wave solution, which describes the advancing front of a phase transformation in an infinite domain, is found.